(untitled) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2024)
Computational thinking (CT) is a crucial skill for students in their daily lives. However, students’ CT abilities remain relatively low, necessitating effective solutions to enhance these skills in the learning process. This study aims to implement a problem-based learning (PBL) model using unplugged media in Informatics subjects to improve students’ computational thinking skills, particularly in learning data structures, specifically Stack and Graph concepts. The results showed an improvement in students’ learning outcomes, with gain score analysis indicating moderate improvement in computational thinking skills. The findings suggest that integrating a problem-based learning model with unplugged media effectively enhances students’ computational thinking abilities, particularly in understanding Stack and Graph data structures.